2003
DOI: 10.1016/s0168-9002(03)02014-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of radiation damage in lead tungstate crystals using intense high-energy beams

Abstract: We report on the effects of radiation on the light output of lead tungstate crystals. The crystals were irradiated by pure, intense high energy electron and hadron beams as well as by a mixture of hadrons, neutrons and gammas. The crystals were manufactured in Bogoroditsk, Apatity (both Russia), and Shanghai (China). These studies were carried out at the 70-GeV proton accelerator in Protvino.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Tests were recently performed on PWO at IHEP Protvino [6] for the BTeV experiment and at CERN and ETH-Zürich [7] for the CMS ECAL.…”
mentioning
confidence: 99%
“…Tests were recently performed on PWO at IHEP Protvino [6] for the BTeV experiment and at CERN and ETH-Zürich [7] for the CMS ECAL.…”
mentioning
confidence: 99%
“…These studies have revealed that the formation and remediation of radiation damage in crystals and the signal level depend strongly on the surrounding temperature [4,5]. They have also revealed deep suppression of the restoration processes in the crystal at negative temperature [6].…”
Section: Target Spectrometermentioning
confidence: 96%
“…In this paper we investigate the possible change in light emissions in the crystals which would be a more serious change than the loss of transmission as the transmission does recover in time [5] This paper report results of two such studies.…”
Section: Introductionmentioning
confidence: 99%
“…Indirectly, we have already addressed this issue in our previous study [5]. We measured non-uniformity of the light output along the crystal by exposing the crystals to a muon beam perpendicular to the axes of the crystals.…”
Section: Introductionmentioning
confidence: 99%